Economic View and Strategic Management View toward Understanding Outsourcing in Amateur Sport - Lee, Seungbum (Journal of Amateur Sport, 2016)
Outsourcing as a strategic business decision has been a prevalent business practice in sport industry, and as a result has been receiving increasing academic attention by scholars in sport management. In many cases, the academic attention has been focused on multi-billion dollar hyper-commercialized sport industry, like professional and intercollegiate sport in the U.S. However, outsourcing has infiltrated the world of amateur sport, for instance youth sports programs (YSP), too. In spite of a growing use of outsourcing as a viable business strategy within a community based sport setting, efforts to understand outsourcing in amateur sport has so far gone unheeded in academia. Accordingly, this study examined outsourcing YSP by city- owned recreation centers (CORC). The motivation of outsourcing and the risk of outsourcing were analyzed using a multiple case study approach. The results of this study argue that combination of both economic and strategic management views are effective ways to understand outsourcing strategies in an amateur sport setting. The findings of this study provide both theoretical and practical implications. Furthermore, to contribute to the body of literature, the findings of this study are compared with previous sport management outsourcing literature to provide a comprehensive understanding of outsourcing.